2009
DOI: 10.1246/bcsj.82.860
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Photophysical Properties of N-Arylcarbazolophanes

Abstract: Two carbazolophanes bearing benzene or naphthalene rings on the nitrogen atoms of carbazole were successfully synthesized by the intramolecular etherification of the precursor tetraols, and their photophysical properties were investigated in detail based on the absorption spectra, fluorescence spectra, fluorescence lifetimes, quantum yields, phosphorescence spectra, and transient absorption spectra. It was concluded that the carbazolophane bearing benzene rings forms carbazole excimer in both excited singlet a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…We have already shown that the strong torsion in the biphenyl unit in compounds 1 − 6 electronically decouples the two halves of the molecule to some degree, resulting in absorption and phosphorescence spectra that are identical to those of N -phenylcarbazole. N -Arylcarbazoles and N -alkylcarbazoles have been studied extensively in the past by Klöpffer, Johnson, and many others, , and it is well-known that they are prone to form excimers. Given the similar electronic structure, it is instructive to compare the excimer emission we find for compounds 1 − 6 with the existing literature on excimers in N -arylcarbazoles and N -alkylcarbazoles.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have already shown that the strong torsion in the biphenyl unit in compounds 1 − 6 electronically decouples the two halves of the molecule to some degree, resulting in absorption and phosphorescence spectra that are identical to those of N -phenylcarbazole. N -Arylcarbazoles and N -alkylcarbazoles have been studied extensively in the past by Klöpffer, Johnson, and many others, , and it is well-known that they are prone to form excimers. Given the similar electronic structure, it is instructive to compare the excimer emission we find for compounds 1 − 6 with the existing literature on excimers in N -arylcarbazoles and N -alkylcarbazoles.…”
Section: Resultsmentioning
confidence: 99%
“…With a view to the ubiquitous use of CBP derivatives as hosts for WOLED applications we note that the well-known propensity of this general class of materials to form excimer states (and the polarity dependence of triplet excimer formation) deserves more attention. 11,[18][19][20][21][22][23][24][25][26][27][28] The presence of poorly emissive triplet excimers by the host can easily go unnoticed, in particular when combined with efficient phosphorescent emitters that cover a broad spectral range as is the case in WOLEDs. Nevertheless, long-lived triplet excimers may present nonradiative decay channels, and they can reduce device efficiency and device lifetime if not suitably managed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation